Elaboración de núcleos proteicos para la alimentación del ganado porcino - Galarza Cortez, Elías Fernando (2022)
This work exposes the methods and ideas for the elaboration of balanced feed for pigs, involving clear and simple approaches on each one of the components that allow to technically reach the nutritional and energetic requirements so that the animal load achieves the expected objectives, therefore the benefits of the use of protein nuclei made in an artisanal way were analyzed, which leads to the pig farmer himself being able to save time and money, and at the same time it is intended to identify the best formulation in terms of their elaboration, obtaining satisfactory conclusions that seek generate possible solutions to increase the value of the balanced formulas that are marketed today. This research socializes a favorable alternative to the small producer so that he prepares the necessary food for his own herd in a responsible and technical way.